Antagonistic action of caffeine against LY294002-induced apoptosis in cerebellar granule neurons - Wang Wen-Ya; Li Ming-Tao; Pi Rong-Biao; Qiu Peng-Xin; Su Xing-Wen; Lin Sui-Zhen; Yan Guang-Mei (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of caffeine on apoptosis induced by inhibition of 1-phosphatidylinositol 3-kinase in cerebellar granule neurons. METHODS: Cerebellar granule neurons culture, agar gel electrophoresis, and stress-activated protein kinase (SAPK)/c-Jun N-terminal protein kinase (JNK) assay kit to measure SAPK/JNK activity. RESULTS: LY294002 evoked apoptosis concentration-dependently in cerebellar granule neurons. But death resulting from LY294002 was prevented by caffeine in a concentration-dependent manner. The survival effect of caffeine was not affected by inhibitors of ryanodine-sensitive Ca2+ release, nor was it inhibited by L-type channel blockers and N-methyl-D-aspartate (NMDA) receptor blocker. In addition, RP-cAMP, H89, and KN62 were not able to inhibit the protective effect of caffeine. Phosphorylation of c-Jun was necessary for the induction of apoptosis induced by LY294002 in cerebellar granule neurons. But caffeine directly inhibited the activation of JNK and decreased phospho-c-Jun in granule neurons. CONCLUSION: Caffeine inhibited the activation of JNK and decreased the phosphorylation of c-Jun to protect granule neurons from LY294002-induced apoptosis.